2020
DOI: 10.1038/s41598-020-68585-z
|View full text |Cite
|
Sign up to set email alerts
|

The anti-glioblastoma effect of cold atmospheric plasma treatment: physical pathway v.s. chemical pathway

Abstract: Cold atmospheric plasma (CAP), a near room temperature ionized gas, has shown potential application in many branches of medicine, particularly in cancer treatment. In previous studies, the biological effect of CAP on cancer cells and other mammalian cells has been based solely on the chemical factors in CAP, particularly the reactive species. Therefore, plasma medicine has been regarded as a reactive species-based medicine, and the physical factors in CAP such as the thermal effect, ultraviolet irradiation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 39 publications
5
57
0
Order By: Relevance
“…Using a novel experimental design, it was found that melanoma cells B16F10 were effectively killed by physical factors mainly the EM effect from a typical CAP jet source [ 20 ]. Similar phenomena have also been observed later during the treatment on glioblastoma cells U87MG, lung cancer cells A549, bladder cancer cells MBT2, MB49, and breast carcinoma cells MDA-MB-231 [ 130 , 131 ]. In these cases, CAP treatment was performed on the bottom of an inverted cell culture dish or a multi-well plate.…”
Section: Necrosissupporting
confidence: 74%
See 3 more Smart Citations
“…Using a novel experimental design, it was found that melanoma cells B16F10 were effectively killed by physical factors mainly the EM effect from a typical CAP jet source [ 20 ]. Similar phenomena have also been observed later during the treatment on glioblastoma cells U87MG, lung cancer cells A549, bladder cancer cells MBT2, MB49, and breast carcinoma cells MDA-MB-231 [ 130 , 131 ]. In these cases, CAP treatment was performed on the bottom of an inverted cell culture dish or a multi-well plate.…”
Section: Necrosissupporting
confidence: 74%
“…Both B16F10 cells and U87MG cells experienced noticeable swell and final burst in it. In contrast, when the physically based CAP-treated B16F10 cells and U87MG cells immediately cultured in deionized water, they indeed experienced clear swell but without finally losing the integrity of cytoplasmic membrane [ 20 , 130 ]. Thus, the mechanical property of cytoplasmic membrane may be enhanced and can even resist the strong osmotic pressure.…”
Section: Necrosismentioning
confidence: 99%
See 2 more Smart Citations
“…130 It is promising that we may see that many new unknows about the biological impact of bulk CAP, such as potential physical effect. 131,132…”
Section: Review Materials Advancesmentioning
confidence: 99%